Development of audiovisual media to improve OSH knowledge among construction workers of PT Sasmito at the construction project of FMIPA building at UGM Yogyakarta - Sekar, Meilana Nawang; Arianto, Machfudz Eko; Saptadi, Julian Dwi (Universitas Ahmad Dahlan, 2023)
Background: Work accidents with a high rate of fatality are dominated by the ones in construction work. Accidents could be caused by a number of factors, one of them is workers’ behavior. Knowledge and audiovisual media are the supporting factors and predispositions that influence workers’ behavior. Some workers have not understood the function of Personal Protective Equipment (PPE) and the standard application of PPE. This study is aimed at finding out the feasibility of audiovisual media and the average level of OSH knowledge among the workers before and after intervention. Method: This is a Level 4 Research and Development (RnD) study consisting of Product Design, Product Validation, Product Revision, and Limited Trial. The sample were the workers of PT Sasmito at the construction project of FMIPA building in UGM Yogyakarta consisting of 40 people. Validity test of the media was conducted by distributing questionnaires to material and media experts. Limited trial was conducted by distributing the questionnaire before and after intervention. Data analysis was carried out using univariate and bivariate analysis, i.e. Wilcoxon sign rank. Results: The total scores resulting from the validity tests were 76% by the material experts and 85% by the media experts, meaning that the audiovisual media was categorized as “feasible” and “highly feasible”. Hence, the audiovisual media was feasible or appropriate to be presented to the construction workers. The average rates of OSH knowledge among the workers were 11.20 for the pre-test and 13.8 for the post-test, respectively. The Wilcoxon Sign Rank test resulted in the p-value of 0.000 (<0.05), meaning that there was a difference in the average rate of OSH knowledge between the conditions of before and after the provision of audiovisual media to the construction workers of PT Sasmito at the construction project of FMIPA building at UGM. Conclusion: Audiovisual media is feasible to be presented and there is a difference in average rate of the workers’ knowledge on the PPE application between the conditions before and after the intervention. Companies are expected to use audiovisual media as a means to promote OSH.